2021
DOI: 10.3390/educsci11120773
|View full text |Cite
|
Sign up to set email alerts
|

From First to First: Black, Indigenous, and People of Color First-Generation Faculty and Administrator Narratives of Intersectional Marginality and Mattering as Communal Praxis

Abstract: While the education of first-generation students (FGS) has garnered the attention of scholars, educators, and policy makers, there is limited dialogue on how first-generation faculty and administrators (FGF/A)—that is, first-generation students who went on to become faculty and/or administrators—experience higher education and are engaged in enhancing equity, inclusion, and justice. Intersectional approaches, which illuminate the nexus of race, gender, and class in education, are necessary for appreciating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Mentorship is broadly defined and includes providing FG, racially marginalized, and working-class students with encouragement, emotional support, advice, academic guidance, and advising (e.g., Longley, 2020;Serravallo, 2018;Swindle, 2018;Warnock, 2016a;Yeskel, 2008). The positive mentorship experiences some FGF have had lead them to value their roles as potential mentors and to want to repay the help they received (e.g., Ciucevich Story, 2008; E. Lee & Maynard, 2017;Mack, 2019;Vue, 2021). For example, one FGF who advised a student organization described conversations with FGCS about disclosing their family backgrounds to peers and how to react to classmates' casual references to their wealth and privilege (Lang, 2016).…”
Section: Theme 4: Seeking Social Networkmentioning
confidence: 99%
See 4 more Smart Citations
“…Mentorship is broadly defined and includes providing FG, racially marginalized, and working-class students with encouragement, emotional support, advice, academic guidance, and advising (e.g., Longley, 2020;Serravallo, 2018;Swindle, 2018;Warnock, 2016a;Yeskel, 2008). The positive mentorship experiences some FGF have had lead them to value their roles as potential mentors and to want to repay the help they received (e.g., Ciucevich Story, 2008; E. Lee & Maynard, 2017;Mack, 2019;Vue, 2021). For example, one FGF who advised a student organization described conversations with FGCS about disclosing their family backgrounds to peers and how to react to classmates' casual references to their wealth and privilege (Lang, 2016).…”
Section: Theme 4: Seeking Social Networkmentioning
confidence: 99%
“…This critical review also revealed limitations in FGF literature, including narrow demographic and social identity representation. Although recent publications underscore the value of attention to FGF of color (Buenavista et al, 2022; Van Galen & Sablan, 2020b; Vue, 2021), much of FGF scholarship focuses on White academics from a narrow set of academic disciplines whose experiences are captured through personal narratives. Thus, we argue that an intersectional understanding is critical for authentic, practical engagement with the long-term implications of FG status, its complexities and complications, and any assumption of a relationship between it and equity-oriented work on behalf of marginalized students (Decoteau, 2016; Farris & De Jong, 2014).…”
Section: Defining “First-generation” Intersectionallymentioning
confidence: 99%
See 3 more Smart Citations